2021
DOI: 10.1155/2021/6617256
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mitophagy in Regulating Cell Death

Abstract: Mitochondria are multifaceted organelles that serve to power critical cellular functions, including act as power generators of the cell, buffer cytosolic calcium overload, production of reactive oxygen species, and modulating cell survival. The structure and the cellular location of mitochondria are critical for their function and depend on highly regulated activities such as mitochondrial quality control (MQC) mechanisms. The MQC is regulated by several sets of processes: mitochondrial biogenesis, mitochondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 159 publications
0
29
0
Order By: Relevance
“…The alteration in SL metabolism associated with spiperone treatment could also contribute to mitochondrial inner membrane depolarization and the reduction in mitochondrial activity observed after long-term treatment with the drug, since it has been demonstrated that excessive sphingolipid accumulation in the mitochondria is associated with complex III irreversible inhibition, inner membrane depolarization, mitochondrial fragmentation, and mitophagy [181][182][183][184]. Moreover, MCU inhibition did not reduce spiperone-induced depolarization, excluding a direct role of ER Ca 2+ influx into the mitochondria through MAMs in the impairment of the mitochondrial function [56,185].…”
Section: Discussionmentioning
confidence: 99%
“…The alteration in SL metabolism associated with spiperone treatment could also contribute to mitochondrial inner membrane depolarization and the reduction in mitochondrial activity observed after long-term treatment with the drug, since it has been demonstrated that excessive sphingolipid accumulation in the mitochondria is associated with complex III irreversible inhibition, inner membrane depolarization, mitochondrial fragmentation, and mitophagy [181][182][183][184]. Moreover, MCU inhibition did not reduce spiperone-induced depolarization, excluding a direct role of ER Ca 2+ influx into the mitochondria through MAMs in the impairment of the mitochondrial function [56,185].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we observed an increase in mtDNAcn in patients with CADASIL, suggesting that mitochondrial dysfunction likely exists in patients with CADASIL, which strengthens evidence provided by previous studies. Due to a lack of self-healing function, mtDNA is usually degraded after being damaged [ 8 , 23 , 24 ], and new mtDNA is synthesized, in response to possible functional defects. For example, several mitochondrial alterations, which include changes in electron transport chain activity, increased oxidative stress and inadequate homeostasis responses, restore normal mitochondrial function and can trigger upregulation of the mtDNA replication machinery [ 5 , 8 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mitophagy, the removal of damaged or unwanted mitochondria, was found to be essential for maintaining cellular fitness [ 71 ]. Previous work by our group demonstrated the role of mitophagy in regulating cell death [ 72 ]. The current review summarizes the relationship between mitophagy and cell death after TBI, as well as mitophagy as a potential therapeutic intervention for altering cell death to improve neurological outcomes.…”
Section: The Role Of Mitophagy In Tbimentioning
confidence: 99%